2015
DOI: 10.1002/anie.201505168
|View full text |Cite
|
Sign up to set email alerts
|

Photon‐Upconverting Ionic Liquids: Effective Triplet Energy Migration in Contiguous Ionic Chromophore Arrays

Abstract: Inspired by the bicontinuous ionic-network structure of ionic liquids (ILs), we developed a new family of photofunctional ILs which show efficient triplet energy migration among contiguously arrayed ionic chromophores. A novel fluorescent IL, comprising an aromatic 9,10-diphenylanthracene 2-sulfonate anion and an alkylated phosphonium cation, showed pronounced interactions between chromophores, as revealed by its spectral properties. Upon dissolving a triplet sensitizer, the IL demonstrated photon upconversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 43 publications
(183 reference statements)
3
52
0
Order By: Relevance
“…This was also supported by the absence of sharp peaks in its synchrotron powder X‐ray diffraction (PXRD) pattern (Figure d). The PXRD pattern also indicated the existence of the bicontinuous network nanostructures in P 66614 PPOS composed of polar ionic and nonpolar alkyl/chromophore domains . The low‐angle peak at 2.7° of P 66614 PPOS was in accordance with those of the precursor IL P 66614 Cl and our previous blue‐emitting chromophoric IL having the same P 66614 cation .…”
Section: Figuresupporting
confidence: 75%
See 2 more Smart Citations
“…This was also supported by the absence of sharp peaks in its synchrotron powder X‐ray diffraction (PXRD) pattern (Figure d). The PXRD pattern also indicated the existence of the bicontinuous network nanostructures in P 66614 PPOS composed of polar ionic and nonpolar alkyl/chromophore domains . The low‐angle peak at 2.7° of P 66614 PPOS was in accordance with those of the precursor IL P 66614 Cl and our previous blue‐emitting chromophoric IL having the same P 66614 cation .…”
Section: Figuresupporting
confidence: 75%
“…The PXRD pattern also indicated the existence of the bicontinuous network nanostructures in P 66614 PPOS composed of polar ionic and nonpolar alkyl/chromophore domains . The low‐angle peak at 2.7° of P 66614 PPOS was in accordance with those of the precursor IL P 66614 Cl and our previous blue‐emitting chromophoric IL having the same P 66614 cation . The distance of 1.75 nm corresponds to the separation between the ionic domains, which is mainly determined by the size of the bulky cation …”
Section: Figuresupporting
confidence: 72%
See 1 more Smart Citation
“…In order to realize a much closer stacking of the emitter, Hisamitsu et al used ionic liquids (ILs) that contain closely packed charged chromphores. 105 In their work, the sulfonated DPA anion IL1 (Fig. 7) was used with an alkylated phosphonium countercation, eliminating alkyl chains.…”
Section: à2mentioning
confidence: 99%
“…9−11 Only non-coherent, dim light is required for TTA upconversion, and it has been shown that photoexcitation power densities as low as only a few mW cm −2 is sufficient, such that solar irradiation can also be used. 12,13 Since TTA upconversion systems typically exhibit strong absorption of photoexcitation, upconversion quantum yields as high as 20−30% can be achieved. Furthermore, absorption and emission wavelengths can be synthetically tuned, 1,2 and upconversion system can be readily tagged to various matrices, including nanoparticles, 14 microemulsions, 15 and microcapsules.…”
Section: Introductionmentioning
confidence: 99%